James Blundell and the Edinburg Trace in the Development of Hemotransfusion (the Authors’ Own Study) - Ye. M. Shifman; G. V. Filippovich (Общая реаниматология)
This paper is simultaneously a brief biographic sketch of British obstetrician James Blundell (1970—1878) and an attempt of the authors to open new earlier unknown pages of the history of hemotransfusion. This paper presents James Blundell not only as a physician who was the first to successfully transfused blood from man to man, but also as an outstanding obstetrician and a founder of pediatric reanimatology. The paper places great emphasis on Blundell’s predecessors undeservedly forgotten by medicine historians, on Doctor John Henry Leacock in particular. The empirical stage in the development of hemotransfusiology was over due to the performance of a number of animal experiments on blood transfusion by this physician in 1816. Unfortunately, information has not been at the disposal of even foreign investigators and it will be first published for Russian language-speaking readers.